Pelatihan Junior Network Administrator Untuk Siswa SMK Kabupaten Kuningan Dalam Menghadapi Era Digital - Khaerul Anam; Ryan Hamonangan; Andrian Maulana; Astri Gita Lestari (CV. Multi Kreasi Media, 2024)
The availability of competent human resources in network administration is a crucial need in the digital era. This Community Partnership Program focuses on providing junior network administrator training for Vocational High School (SMK) students in Kuningan Regency. The aim of this training is to enhance students' competence in managing and maintaining computer network infrastructure. The training material covers understanding network concepts, configuring network devices, basic network security, and simple troubleshooting abilities. Through this program, it is expected that SMK students in Kuningan Regency will have adequate preparation to develop careers in the field of information technology after graduation.